2021
DOI: 10.1088/1742-6596/1940/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nutritional Content of Water Spinach (Ipomoea aquatica) Cultivated Hydroponically and Non-Hydroponically

Abstract: Water spinach is well known by our society as a green vegetable that has a high vitamin mineral content at a low price and is easy to obtain and its cultivation is also relatively easy. This character supports the development as a potential horticultural crop commodity to be developed. The main source of vitamins is leafy green vegetables. Leaf green vegetables can be cultivated non-hydroponically and hydroponically. In vegetables there is beta-carotene which is the initial form of vitamin A so it is called pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…However, Fevria et al also reported the addition ecoenzyme liquid into spinach (Amaranthus sp. ), which cultivate by hydroponically, showed vitamin C levels increased significantly [13].…”
Section: Resultsmentioning
confidence: 95%
“…However, Fevria et al also reported the addition ecoenzyme liquid into spinach (Amaranthus sp. ), which cultivate by hydroponically, showed vitamin C levels increased significantly [13].…”
Section: Resultsmentioning
confidence: 95%
“…The decrease in NAR affects reduced in RGR of plant. As explained by Francescangeli et al, (2006) and Osone et al, (2008) that decrease in RGR was caused by increase in LA which caused LAI to increase, so that reducing photosynthesis rate and increasing respiration rate, which caused that use more assimilate.…”
Section: Resultsmentioning
confidence: 99%
“…Untuk pembelajaran biologi, kewirausahaan dapat dikembangkan melalui penciptaan produk-produk biologi pada materi pembelajaran bioteknologi (4,5). Bioteknologi dalam arti luas merupakan teknik yang menggunakan organisme untuk membuat atau memodifikasi produk (6). Pengintegrasian muatan nilai-nilai kewirausahaan kedalam bidang ilmu hayati seperti bioteknologi dikenal dengan istilah bioentrepreneurship (3,7).…”
Section: Pencapaianunclassified